HISTORY TOMB OF DATUK ABDURRAHIM BIN ABU BAKAR IN LATENG, BANYUWANGI, EAST JAVA AS A HISTORY LEARNING SOURCE IN BANYUWANGI 1 STATE HIGH SCHOOL - Asy'ari, Faruq Hasan; Ediyono, Suryo (Universitas Negeri Yogyakarta, 2022)
Datuk Abdurrahim Bin Abu Bakar is known as a preacher of Islam, namely spreading Islam in various areas, especially Banyuwangi. Every day, the tomb of Datuk Abdurrahim Bin Abu Bakar is never empty of pilgrims who come from various regions with different goals and motivations. The tomb, which is located not far from the city center of Banyuwangi, is very sacred to the people of Banyuwangi. This is very unique, because usually the graves that are sacred to the community are located in forests, hills, and beaches, which are far from residential areas. The further uniqueness of the name of the tomb itself. At the beginning of the name there is the word